2021
DOI: 10.1094/pdis-03-20-0556-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Gaeumannomyces radicicola Causing Stalk Rot on Maize in Brazil

Abstract: Maize (Zea mays L.) is one of the most important commodities, and Brazil is the second-largest maize exporter country in the world. In April 2019, the period of the second crop maize (safrinha), it was observed black decayed lesions on roots and wilting of some maize plants, causing a "sudden death" in a commercial area in the west of Paraná state, Brazil (Figure 1A-C). Symptomatic root and stalk were collected, and tissues surface disinfected with 70% ethanol for 30 s, 1.5% NaOCl for 1 min and rinsed three ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that species M. hyalina was considered as food to decomposer animals in the soil, and can colonize the roots of Arabidopsis and suppress diseases ( Maraun et al, 1998 , 2003 ; Johnson et al, 2019 ). Furthermore, 16 pathogenic fungal species that are detrimental to plant growth were identified in this study ( Rojo et al, 2007 ; Kazan et al, 2012 ; Carraro et al, 2021 ), with the relative abundance of maize pathogenic fungus species G. radicicola being higher in RS and RT than in SS ( Supplementary Table 4 ). Some symbiotic plant growth promoting fungi (PGPF) may form ideal dispersal networks in the rhizosphere soil to aid in rhizobia enrichment, which may explain the higher relative abundance of M. hyalina in the niches SS and RS, while the interaction between non-symbiotic PGPF and plant roots is still poorly understood ( Pieterse et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been demonstrated that species M. hyalina was considered as food to decomposer animals in the soil, and can colonize the roots of Arabidopsis and suppress diseases ( Maraun et al, 1998 , 2003 ; Johnson et al, 2019 ). Furthermore, 16 pathogenic fungal species that are detrimental to plant growth were identified in this study ( Rojo et al, 2007 ; Kazan et al, 2012 ; Carraro et al, 2021 ), with the relative abundance of maize pathogenic fungus species G. radicicola being higher in RS and RT than in SS ( Supplementary Table 4 ). Some symbiotic plant growth promoting fungi (PGPF) may form ideal dispersal networks in the rhizosphere soil to aid in rhizobia enrichment, which may explain the higher relative abundance of M. hyalina in the niches SS and RS, while the interaction between non-symbiotic PGPF and plant roots is still poorly understood ( Pieterse et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the differential distribution of these two bacteria at various sampling stages could partially account for the changes in the C and N content of maize. In addition, we were surprised to discover that the prevalence of the maize pathogen that causes stalk rot, G. radicicola ( Carraro et al, 2021 ), gradually increased throughout the maize growth cycle (from jointing to flowering to maturation) ( Supplementary Table 4 ). According to a recent study, plant developmental stage primarily drives the differentiation in ecological role of the maize microbiome, for example, the beneficial bacterial taxa such as Burkholderiaceae and Rhizobiaceae in plant microbiomes were enriched at the early stage, whereas saprophytic fungi were enriched at the later stage ( Xiong et al, 2021 ), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%